TEACHING AS A FACTOR OF VALUE EDUCATION: INSIGHT INTO AXIOLOGICAL MEANING - Vasiliauskas, Romanas (Acta Paedagogica Vilnensia, 2011)
The topicality and the perfection of learning as a holistic process is raised and analysed in the article in the context of the age of information, constant change and globalisation. Particular attention is drawn to learning as cognition, emotional and social process and its influence on the holistic development of a student. The analysis of teaching is separated into two parts – the traditional approach, focused on teaching and remembering the knowledge, and the next one – oriented to the students and supported on the main ideas. Interaction in teaching–learning process is suggested as a central concept where the active role of the student is emphasized. Data analysis shows that the core of learning is centred at the student’s education in which students learn the best and actively construct their own meaning. The quality of learning is strongly determined by how the student finds the meaning of teaching and how he acquires values. The close association between quality of learning and education of values are known as the basis for teaching strategy. There is an attempt to define strategy of integration of values in teaching which involves school subjects, teaching based on different ages and grades and various methods of teaching values.